nlp - Bavister, Steve, author 555926; Vickers, Amanda, author 555924 (London, England : Hodder Education, 2004)
Are you new to Neuro Linguistic Programming? Do you want a better understanding of what makes you and others tick? Are you seeking clearer goals, more effective communication and better relationships? This book offers straightforward access to understanding LP - the study of subjective experience - and helps you to put the ideas and techniques into practice in your personal and professional life. Exercises, activities, case studies, anecdotes and quizzes are used to bring each area to life. Business-related applications should be evident throughout, and the book is relevant for anyone seeking a solid grounding in NLP, covering NLP practioner level training and beyond. NLP gives you straightforward access to understanding Neuro-Linguistic Programming - one of the most powerful forms of applied psychology available today - and helps you to put the ideas and techniques into practice in both your personal and professional life. If you would like to be more effective, connect with people more easily, and have the opportunity to live your dreams, this book is for you.